Cost-effectiveness evaluation of neonatal emergency transport organization in Italy - Carlo Bellini; Maurizio Gente; Diego Minghetti; Luca A. Ramenghi (Global Pediatrics)
Objective: The aim of this study was to evaluate the cost-effectiveness of the Italian Neonatal Emergency Transport Service (NETS), to analyse its current organisation and to identify potential financial benefits from improvements. Methods: Using data from the 2023 national NETS survey conducted by the Italian Society of Neonatology, regional cost-effectiveness of operating the system were calculated. These were compared with ideal costs for on-call and dedicated NETS models, based on a previously established methodology. Results: The total cost of operating NETS in Italy was €32,785,650. Of this, €24,964,050 was associated with services organised according to the on-call model, while €7,821,600 was associated with dedicated services. The cost per transport varied considerably between regions. The national median cost for on-call services was €7,386 (ranging from €1,809 to €76,209), while the national median cost for dedicated services was €2,421 (ranging from €2,073 to €2,770). The actual total cost could be reduced to the ideal cost of €15,304,308, with the ideal cost per individual transport being €2,450 for on-call services and €2,250 for dedicated services (compared to the current medians of €7,386 and €2,421, respectively). Conclusions: The study concluded that the Italian NETS organisation is expensive and unsustainable due to limited financial resources, and requires a complete overhaul. The implementation of a more cost-effective 'hub-and-spoke' NETS network system could significantly improve financial sustainability. The findings suggest that improvements to the NETS organisation are needed not only in Italy, but potentially across Europe.